Injector sharing among inpatient heroin abusers and related properties - Evren, Cüneyt; Çakmak, Duran (Journal of Dependence, 2002)
Objective: Injector sharing is an important risk factor for spread of infections like AIDS and Hepatitis. The aim of this study was to determine prevalence of injector sharing in heroin abusers who use heroin by intravenous route and related socio-demographic and clinical properties.Method: A semi-structured socio-demographic form, which was formed of questions about substance use characteristics, was applied to 361 inpatient heroin abusers who use heroin by intravenous route. The study was done at the AMATEM clinic, in the year of 2001.Results: A total of 50.3% of the patients reported having shared injector at least once in a lifetime. Mean of age was found to be lower among those who share injectors (27.18 7.07), than those who do not share injectors (31.23 8.86). It was found that first age of drug use and age of starting heavy drug use was early and drug use period was shorter among those who share injectors. The proportion of being single and having treatment by green card was higher among those who share injectors.Conclusion: The rate of self-reported injector sharing is high in the study group. Studies to determine prevalence of this issue and risk factors related with injector sharing will be a base of interventions for reduction of injector sharing. Those who recently started to use injector or those who are at the risk of starting to use injector must be targets of harm reduction interventions. Especially using educational interventions about harm reduction is important for public health issues.
Keywords: Drug abuse; heroin; intravenous drug use; injector sharing